You can do this two ways:
a^2 - b^2 = (a - b)(a + b)
In this case...
a = 3x - 4
b = 2x + 3
So....
a - b
= 3x - 4 - (2x + 3)
= 3x - 4 - 2x - 3
= x - 7
a + b
= 3x - 4 + 2x + 3
= 5x - 1
Now you have
(x - 7)(5x - 1)
= 5x^2 - 35x - x + 7
= 5x^2 - 36x + 7
************
or....
(3x - 4)^2
= 9x^2 + 2(3x)(-4) + 16
= 9x^2 - 24x + 16
(2x + 3)^2
= 4x^2 + 2(3)(2x) + 9
= 4x^2 + 12x + 9
(9x^2 - 24x + 16) - (4x^2 + 12x + 9)
= 5x^2 - 36x + 7
2007-07-03 06:57:32
·
answer #1
·
answered by Mathematica 7
·
0⤊
0⤋
Part 1: (3x-4)(3x-4) = 9x^2 - 24x + 16
Part 2: (2x+3)(2x+3) = 4x^2 + 12x + 9
Part1 - Part 2 = 5x^2 -36x + 7
2007-07-03 13:55:05
·
answer #2
·
answered by khaoticwarchild 3
·
0⤊
1⤋
(3x-4)^2 - (2x+3)^2
square each number accordingly
(9x+16) - (4x+9)
combine like terms accordingly to get the answer
5x + 7
GOOD LUCK
2007-07-03 14:05:21
·
answer #3
·
answered by lesey3 1
·
0⤊
0⤋
Difference of two squares.
a^2 - b^2 = (a+b)*(a-b)
So your expression factors to
(3x-4+2x+3) * (3x-4-2x-3)
= (5x-1)*(x-7)
2007-07-03 13:52:38
·
answer #4
·
answered by Dr D 7
·
6⤊
0⤋
(3x - 4)(3x-4)-(2x+3)(2x+3)
9x^2 - 24x + 16 - 4x^2 - 12x - 9
= 5x^2-36x+7
=(5x - 1)(x - 7)
2007-07-03 13:53:49
·
answer #5
·
answered by miggitymaggz 5
·
0⤊
1⤋
= (9x² - 24x + 16) - (4x² + 12x + 9)
= 5x² - 36x + 7
2007-07-07 02:56:39
·
answer #6
·
answered by Como 7
·
0⤊
0⤋
Hi,
(3x-4)² -(2x+3)² =
(3x - 4)(3x - 4) - (2x + 3)(2x + 3) =
9x² - 12x - 12x + 16 - [4x² + 6x + 6x + 9] =
9x² - 24x + 16 - [ 4x² + 12x + 9] =
9x² - 24x + 16 - 4x² - 12x - 9 =
5x² - 36x + 7 <== answer
I hope that helps!! :-)
2007-07-03 13:52:20
·
answer #7
·
answered by Pi R Squared 7
·
0⤊
5⤋
like this?
5·x^2 - 36·x + 7
sorry, didn't get you... can't be much simpler than that I think.
???
2007-07-03 13:56:10
·
answer #8
·
answered by Anonymous
·
0⤊
1⤋